The parable of the merciful neighbour: A dialogic reading of Luke 10:25–37 - Saleh, Jurgoi; Hombana, Mphumezi (Hervormde teologiese studies, 2025)
This study examines the culture of purity and pollution in first-century Palestine through a close reading of Luke 10:25–37, allowing the cultural setting to provide a cohesive framework for interpreting the parable. It argues that the parable reflects boundary markers that defined who and what was considered clean or unclean, pure or impure, inside or outside and honourable or shameful in ancient Roman Palestine. This framework is then applied to Luke’s use of the parable, where he highlights the contrast between the failure of two temple-centred Jewish figures, who avoid the risk of defilement that might come from tending to a possible corpse, and the courage of the Samaritan, who cares for the wounded man despite the danger of potential community retaliation. In this way, the parable challenges its audience by showing how Jesus redirects the lawyer’s question from the somewhat self-protective ‘Who is my neighbour?’ to the more merciful and reciprocal ‘To whom must I become a neighbour?’ContributionThe study concludes with some hermeneutical reflections on the theme in African society, which has largely been characterised by these ancient attributes.